2016
DOI: 10.5713/ajas.16.0691
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, nutrients digestibility, and blood metabolites of lambs fed diets supplemented with probiotics during pre- and post-weaning period

Abstract: ObjectiveTwo experiments were conducted to evaluate the effects on growth performance, digestibility, and blood metabolites of lambs during pre- and post-weaning period of inclusion of a commercial probiotic (PRO) containing a mixture of two strains of Pediococcus, Pediococcus acidilactici (1×106 colony-forming unit [cfu]/g) and Pediococcus pentosaceus (1.3×106 cfu/g), with dextrose as the carrier compound compared to a diet based on concentrate mixture and wheat straw.MethodsIn exp. 1, 24 male lambs of about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 24 publications
6
40
0
5
Order By: Relevance
“…The present results also showed that both MPP and MPL treatments possessed a significant effect on productivity, reproductive performance and metabolic profiles of Barki ewes. The results obtained concerning the utilization of dry matter and other nutrients in groups with MPP and MPL were in agreement with those reported by Saleem et al (2017) who obtained that dry matter intake nutrients digestibility of lambs were positively influenced by adding different levels of probiotics supplementation. Also, Gomaa et al (2016) found that treated rice straw by bacterial enzymes (MPL) led to improve total digestible nutrient, digested crude protein and nitrogen balance of sheep.…”
Section: Feed Intake and Live Body Weight Changes Of Barki Ewessupporting
confidence: 91%
“…The present results also showed that both MPP and MPL treatments possessed a significant effect on productivity, reproductive performance and metabolic profiles of Barki ewes. The results obtained concerning the utilization of dry matter and other nutrients in groups with MPP and MPL were in agreement with those reported by Saleem et al (2017) who obtained that dry matter intake nutrients digestibility of lambs were positively influenced by adding different levels of probiotics supplementation. Also, Gomaa et al (2016) found that treated rice straw by bacterial enzymes (MPL) led to improve total digestible nutrient, digested crude protein and nitrogen balance of sheep.…”
Section: Feed Intake and Live Body Weight Changes Of Barki Ewessupporting
confidence: 91%
“…Recently it was reported that serum biochemistry is a useful tool in the clinical diagnosis of various systemic states and growth performance of lambs (34). We have observed significantly higher blood concentrations of ALT and ALP in SG lambs compared to FG lambs.…”
Section: Type Of Parasitic Oocysts/eggsmentioning
confidence: 50%
“…Studies have shown that probiotics can enhance antioxidant ability [ 40 , 41 ]. Consistent with our results, the findings showed that serum antioxidant abilities were significantly enhanced while using L. plantarum [ 42 ], L. johnsonii BS15 [ 43 ] and yeast [ 44 ].…”
Section: Discussionmentioning
confidence: 99%